PENGARUH MODEL PEMBELAJARAN PETAK UMPET TERHADAP MOTIVASI BELAJAR PPKn SISWA KELAS VIII SMPN 18 PEKANBARU KECAMATAN SENAPELAN KOTA PEKANBARU - Amina, Siti; Zahirman, Zahirman; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The research background was related to the lack of motivation to learn PPKn on 8th grade students at SMPN 18 Senapelan Pekanbaru kecamatan senapelan kota Pekanbaru. The problem formulation is: “is there any effect on the use of hide and seek learning model toward students’ learning motivation?”. This study aims to determine the effect of hide and seek learning model upon learners’ motivation. Using experimental research with descriptive-qualitative approach, the sample was taken based on the